Coaching in undergraduate medical education: a national survey. Issue 1 (1st January 2020) - Wolff, Margaret; Hammoud, Maya; Santen, Sally; Deiorio, Nicole; Fix, Megan
ABSTRACT: Background : Evidence to support coaching in medical education has grown over the past decade leading educators to search for resources to aid the development of their own coaching programs. A sample of medical schools in the USA were surveyed to describe coaching programs to assist other institutions in the development and implementation of programs. Methods : Participants representing 32 medical schools attending a coaching conference in October 2018 were surveyed via email regarding their undergraduate medical education (UME) coaching programs. The 19-item instrument contained questions on program demographics, program characteristics, coach characteristics, coach training and coach assessment and program evaluation. Results : The response rate was 100% (32/32 programs). Nearly all respondents had a coaching program (53%, 17/32) or were developing one (44%, 14/32) with the majority being implemented in the past five years (82%, 14/17). Professional identity formation (80%, 20/25), professionalism (76%, 19/25), and academic performance (76%, 19/25) were the most commonly identified programmatic goals. The majority of coaches (64%, 16/25) received between 5-25% full time equivalent effort to support their role. Coaches did not formally assess students in any domain at most programs (84%, 21/25) or directly observe their students clinically (76%, 19/25). The majority of programs had formal coach training (88%, 22/25). Conclusion : These results demonstrate that coaching is being used to improve performance, professionalism, and professional identity formation in UME. This sample of coaching programs informs the discussion of coaching in medical education as educators strive to implement effective coaching programs.